Analisis Sensor dan Pelarangan Buku Pada Perpustakaan Nasional Proklamator Bung Hatta - Sri Wahyuni (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2023)
Censhorship and prohibition of books should be done in the library so that it can provide information of an educational nature and have value relevant to the needs of librarians. The study aims to analyze the prohibition and sensing activities of library materials in the National Library of Proclamator Bung Hatta Bukittinggi. The type of research used in this research is qualitative with descriptive analysis. Sampling techniques use purposive sampling with specific criteria to answer research problems. Primary data sources are obtained from the procurement head, librarians, and library publishers. The data collection methods that the researchers use are observations, interviews, and documentation. Then the data analysis, i.e., data reduction, after submitting the subsequent conclusion drawings to disaggregate the results of the research A data validity test using source triangulation aims to check the validity of the data, whether or not it is valid from the source. The results show that the Prolamator Bung Hatta National Library has carried out book censorship activities based on UUD 1945 Alenia 4, Act No. 4 of 1990 on the surrender of printed and recorded works, and Law No. 43 of 2007 on libraries. The three rules of law—these invitations are consistent with each other. In connection with the prohibition of the books, the authorities were not authorized to prohibit public access to the books but to restrict the age and purpose of the readers in order not to misuse the information.